Skills-biased labour demand and the pursuit of inclusive growth in South Africa - Haroon Bhorat; Sumayya Goga; Benjamin Stanwix (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper examines the changing nature of occupational labour-market trends in South Africa and the resulting impact on wages. We observe high levels of demand for skilled labour that have intensified a trend already established before 1994. Over the period 2001-12 employment within the primary sectors collapsed, employment in the manufacturing sector did not increase, while employment in the tertiary sectors such as financial services and community services grew. High- and medium-skilled occupations such as managers, professionals, service and sales workers have seen significant growth while the number of low-skilled workers, and the proportion of medium-skilled workers in the primary and secondary sectors of the economy have declined. In addition, an analysis of occupation demand using a Katz-Murphy decomposition model further shows that within-sector shifts outweigh between-sector shifts in explaining changes in relative labour demand. Increasing demand for skilled labour has also fed into and changed the structure of wages, and therefore wage inequality. We follow the work by Firpo et al. (2011) in an attempt to explore the way in which the returns to certain tasks (rather than occupations) have changed over time. This approach emphasizes the influence of structural factors such as technology and trade, in the presence of increasingly routinized tasks and offshoring, on wages. We run quantile regressions which suggest that, when controlling for age/experience, race and education, jobs which involve automated or routine tasks and those without any face-to-face component (largely lower- to medium-skilled jobs) have seen declining wage levels over time.
Keywords: E24; J21; J24; O14; O55; 330; skills; employment; South Africa; wages; occupations